Disability, medicine and widening participation: A whole system approach. - Coyle, Maeve (Medical Education, 2023)
When thinking about disability, inclusion and medical education, Coyle calls on stakeholders to pay explicit attention to the cultural context of medicine, where people with disabilities are still framed within discourses of deficit.